Pengaruh pH , konsentrasi isolat chlorella vulgaris dan waktu pengamatan terhadap tingkat cemaran limbah cair crumb rubber - Rindit Pambayun, Chasri Nurhayati, Basuni Hamzah, (Jurnal Dinamika Penelitian Industri, 2014)
The purpose of this study was to determine the influence of microalgae concentration, pH and time of observation of the levels of pH, biochemical oxygen demand (BOD), chemical oxygen deman (COD), total suspended solids (TSS), and  ammonia on crumb rubber waste water. This study use the Completely Randomized Design-factorial which consisting of three factors. The first factor is the concentration of microalgae (K) with K1=5%, K2 =10%, K3=15%  and K4=20%, the second factor is pH (P) with P1=pH7, P2=pH 8, P3=pH 9 and the third factor is the time of observation (W) with the standard of 1,2,3,4,5,6,7,8,9,10. The variables that were observed were pH, BOD, COD, TSS, and ammonia. The results showed that the microalgae concentration, pH and time of observation has significant effect on pH, BOD, COD, TSS, and ammonia. Combination treatment of microalgae concentration of 5% and a pH of 7 and time of 5th observation (K1P1W5) is the best treatment to reduce crumb rubber waste water according to Government Regulation of South Sumatera Number 8 Year 2012 (Per. Gub. Sum.Sel. 8 Th 2012) and Kep.Men. LH No. 51/Men LH/10/1995 with a  pH of 7.72, the BOD of 58.3667 mg/L, COD of 108.5700 mg/L, TSS of 3.0300 mg/L, and ammonia of 3.3500 mg/L. Keywords: crumb rubber waste,  concentration of microalgae, pH AbstrakTujuan dari penelitian ini adalah mengetahui pengaruh konsentrasi mikroalga, pH  dan waktu pengamatan terhadap kadar pH, biochemical oxygen demand (BOD), chemical oxygen deman (COD), total suspended solids (TSS), dan amonia limbah cair crumb rubber. Penelitian ini menggunakan rancangan acak lengkap faktorial  yang terdiri  tiga faktor. Faktor pertama yaitu konsentrasi mikroalga (K) dengan taraf K1= 5%,K2=10%,K3=15% danK4=20%, faktor kedua  yaitu pH  (P)  dengan taraf P1=pH7, P2=pH 8 dan P3=pH 9 dan faktor  ke tiga yaitu waktu pengamatan (W) dengan taraf 1 s/d 10. Peubah yang diamati adalah pH, BOD, COD, TSS, dan amonia. Hasil penelitian menunjukkan  bahwa Kosentrasi mikroalga, pH dan waktu pengamatan  berpengaruh  nyata terhadap pH, BOD, COD, TSS, dan amonia. Kombinasi perlakuan konsentrasi  mikroalga 5% dan pH 7 dan waktu pengamatan  ke-5 (K1P1W5) merupakan perlakuan  terbaik untuk menurunkan  limbah crumb rubber  sesuai Per. Gububernur  Sumatera Selatan . No.8  Tahun 2012 dan Keputusan Menteri Lingkungan Hidup No. 51/Men LH/10/1995 dengan  nilai  pH  sebesar 7,72, BOD sebesar  58,3667  mg/L, COD sebesar 108,5700 mg/L, TSS sebesar 3,0300  mg/L,  dan amonia sebesar  3,3500 mg/L. Kata Kunci: limbah  crumb rubber, konsentrasi mikroalga, pH